Biópsia aspirativa no estudo de lesões torácicas - A. Araújo; F. Magalhães; M.M. Figueiredo; A. Sanches; A. Barros; O. Yeep (Revista Portuguesa de Pneumologia, 1997)
RESUMO: A biópsia aspirativa transtorácica (BAT) é a técnica de eleição no diagnóstico de lesões toracicas, sobretudo quando periféricas e quando suspeitas de serem malignas. Fizemos o estudo retrospectivo de 55 BATs executadas em 53 doentes com lesões de distintos aspectos radiológicos e localizaçõoes várias. A nossa rentabilidade técnica foi de 95,3% nos doentes com patologias malignas. Pensamos que há ainda pontos discutíveis sobre esta técnica, apesar de ela ser actualmente uma manobra de rotina. ABSTRACT: Transthoracic fine-needle aspiration (TFNA) is generally the initial procedure of choice in the evaluation of many pulmonary lesions, especially if they are peripheral and suspected to be malignant. The authors report review on 55 TFNA in 53 patients with different pulmonary lesions after nondiagnostic fiberoptic bronchoscopy.Malignancy was demonstrated in 41 of the 43 patients with malignant pathology (95,3%). In our institution TFNA is a commonly made procedure, accurate, safe and time-effective in the diagnosis of many intrathoracic lesions. Palavras-chave: Biópsia aspirativa transtorácica, Punção aspirativa transtorácica, Lesões intratorácicas, Casuística, Key-words: Transthoracic fine-needle aspiration, Pulmonary lesions